Taking down of evidence by handwriting in a criminal proceeding under the Malaysian Criminal Procedure Code (CPC), and the Syariah Criminal Procedure (state of Selangor) Enactment 2003; is it a mandatory? - Kamarudin, Abdul Rani; Md. Dahlan, Nuarrual Hilal (Malayan Law Journal Sdn Bhd, 2005)
The essence of criminal justice is to see that justice is seen to be done or to seek the manifest truth. Once justice has been substantially seen to be done, the question that an accused has been prejudiced or for that matter, the prosecution have been put to disadvantage does not arise. In this respect, the chief purpose of procedural law is to lay down the rules that criminal justice officials must follow: That persons must be tired not by arbitrary procedures but in accordance to the process outlined in the law is the basic principle of procedural law.